Notions and pesticide use: A case study with family farmers (Research, Society and Development, 2021)
The aim of this study was to know the notions of family farmers about the use of pesticides and identify how this use takes place. This is a case study with a qualitative approach, developed with 13 family farmers from a small town located in southern Brazil. The data were produced using semi-structured interview and non-participant observation techniques and submitted to content analysis in the thematic modality. Farmers' notions about pesticides reveal that they recognized the negative effects because these chemicals are used to control and eradicate pests in crops, therefore, they identified the potential for damage to health and the environment. Furthermore, the results demonstrate that the perceptions were anchored in the beneficial effects of the use of pesticides. The use of pesticides reveals the occupational exposure of farmers and their families and reflects a context of vulnerability in which these farmers and their families find themselves. Although these farmers have technical assistance, there are difficulties that need to be overcome, such as the difficulty of communication and understanding and the use of personal protective equipment.